2009
DOI: 10.1111/j.1863-2378.2008.01177.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii Among Nunavik Inuit (Canada)

Abstract: As a result of their intimate contact with the land and their nutritional habits, the Inuit of Nunavik are considered to be at risk from zoonotic infections. To better understand the risk factors for Toxoplasma gondii infection, a serosurvey was conducted in Nunavik, Québec, in September 2004. A representative sample of the Inuit adult population of Nunavik participated in this cross-sectional study (n = 917). Antibodies (IgG) against T. gondii were detected by immunoassay. Information on sociodemographic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 30 publications
4
50
2
3
Order By: Relevance
“…Immigrant populations are considered high risk, which may explain why urban core areas in this study reported higher incidence rates than areas with fewer new immigrants. 5,25 In contrast to serological surveys in northern Canada, which found that more females had been exposed than males, 10 our analysis found that a significantly higher proportion of males developed serious toxoplasmosis than females. HIV infection, a risk factor for the development of serious toxoplasmosis disease, is more prevalent among men than women in Canada (0.32% among men, 0.096% among women).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Immigrant populations are considered high risk, which may explain why urban core areas in this study reported higher incidence rates than areas with fewer new immigrants. 5,25 In contrast to serological surveys in northern Canada, which found that more females had been exposed than males, 10 our analysis found that a significantly higher proportion of males developed serious toxoplasmosis than females. HIV infection, a risk factor for the development of serious toxoplasmosis disease, is more prevalent among men than women in Canada (0.32% among men, 0.096% among women).…”
Section: Discussioncontrasting
confidence: 99%
“…5 The national incidence rate for toxoplasmosis is unknown for Canada, although various seroprevalence estimates in indigenous communities have been reported (3-65%). 10,11 In the United States, one case of TE has a direct treatment cost of approximately US$10,379 (1992 U.S. dollars), and overall economic losses associated with congenital toxoplasmosis are estimated at US$0.4-8.8 billion annually. 6 This latter estimate takes into account medical costs (≈US$45 million/year), income losses scaled to the level of disability (US$2.8 billion/year), and special residential/education needs due to mental or physical impairment (US$2.4 billion/ year over a 40-year lifespan).…”
Section: Introductionmentioning
confidence: 99%
“…29,30 In northern Canada, risk factors include female gender, increasing age, frequency of fishing, berry picking, bird handling, cleaning domestic water reservoirs, and consumption of marine mammals, fish, and birds. 31 In our communities, we observed many cats living outdoors, where hunting and eating intermediate hosts (i.e., rodents, birds) is a likely source of infection. Approximately one-fifth of human participants were involved with hunting/trapping and skinning/ butchering activities, with approximately equal representation between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] More recently, surveillance of people residing in northern Indigenous communities across Canada has raised concerns regarding the seroprevalence of exposure to parasitic zoonoses, including Echinococcus, Toxoplasma, Trichinella, and Toxocara. 2,[6][7][8][9][10][11] Companion animals, such as dogs, act as bridging hosts between wildlife and people, and they can serve as sources of human infection with Echinococcus spp., T. canis, and zoonotic genotypes of Giardia through shedding infective parasite eggs and cysts in feces. [12][13][14] For other parasites, such as Toxoplasma, Trichinella, and Diphyllobothrium, dogs may serve as sentinels of shared environmental risks for humans consuming the same wild game or fish.…”
Section: Introductionmentioning
confidence: 99%